The utility of speckle-tracking echocardiography in early and midterm follow-up after anomalous origin of the left coronary artery from the pulmonary artery repair - Mani Ram Krishna; Kaushik Jothinath; Vijay Kumar Raju (Wolters Kluwer Medknow Publications, 2023)
Anomalous left coronary artery from the pulmonary artery (ALCAPA) is a reversible cause of left ventricular (LV) dysfunction in infants. The LV function is expected to improve serially and return to normal by 1 year after surgical repair. The pattern of improvement in LV function has not been serially analyzed after ALCAPA repair. We report our preliminary experience with serial assessment of LV function in infants undergoing ALCAPA repair utilizing speckle tracking echocardiography.